Student Entrepreneurial Intention: Entrepreneurial Motivation and Individual Entrepreneurial Orientation as Mediation - Melda Anggraini; Fatmah Bagis; Naelati Tubastuvi; Rifka Utami Arofah (International Journal of Economics, Business and Innovation Research, 2025)
Entrepreneurship is one of the important factors in economic growth in every country. Young generations, such as university students have become subjects in the growing entrepreneurship. studying the factors that influence their willingness to innovate and improve their competencies related to entrepreneurship. This study aims to empirically test a research model that investigates the impact of individual entrepreneurial orientation and entrepreneurship education on entrepreneurial intentions. The population in this study was 1793 and the samples used ware of 327 current business economics academic members from three most prestigious universities in Purwokerto, Indonesia, participated in study. Questionnaires were given directly, and sampling was carried out utilizing accidental approaches that satisfied necessary requirements. Partial Least Squares (PLS) is then used to examine gathered data. The results of the analysis show that hypotheses ne to six hypotheses studied have a positive influence on entrepreneurial intentions and the results of hypotheses seven to eleven state that entrepreneurial motivation and individual entrepreneurial orientation are able to mediate, it shows that with the support of these factors students will tend to have the intention to become entrepreneurs in the future. Keywords:Entrepreneurial Intentions, Individual Entrepreneurial Orientation, Entrenreneurship Education, Entrepreneurial Motivations.